Increased TPSAB1 Copy Number in a Family With Elevated Basal Serum Levels of Tryptase - Hernández-Hernández, Laura; Sanz, Catalina; Marcos-Vadillo, Elena; García-Sánchez, Asunción; Moreno, Esther; Lorente, Félix; González-de-Olano, David; Dávila, Ignacio; Isidoro-García, María (Frontiers in Medicine, 2021)
Background: Some recent familiar studies have described a pattern of autosomal dominant inheritance for increased basal serum tryptase (BST), but no correlation with mRNA expression and gene dose have been reported. Objective: We analyzed the TPSAB1 mRNA expression and gene dose in a four-member family with high BST and in two control subjects. Methods: Blood samples were collected from the family and control subjects. A complete morphologic, immunophenotypical and molecular bone marrow mast cell studies were performed. mRNA gene expression and gene dose were performed in a LightCycler 480 instrument. Results: The elevated total BST in family members correlated with a significant increase in tryptase gene expression and gene dose. Conclusions and Clinical Relevance: We present a family with elevated BST that correlated with a high expression of tryptase genes and gene dose. The main relevance is that not always serum elevated basal levels of tryptase means that the patient has a mast cell disorders. Clinicians should be aware that there are cases of familial hypertriptasemia.